The possibility of culture : pleasure and moral development in Kant's aesthetics - Murray, Bradley, 1980-; Ohio Library and Information Network (Chichester, West Sussex, UK ; Malden, MA : Wiley, 2015)
The Possibility of Culture: Pleasure and Moral Development in Kant's Aesthetics presents an in-depth exploration and deconstruction of Kant's depiction of the ways in which aesthetic pursuits can promote personal moral development. Presents an in-depth exploration of the connection between Kant's aesthetics and his views on moral development Reveals the links between Kant's aesthetics and his anthropology and moral psychology Explores Kant's notion of genius and his views on the connections between the social aspects of taste and moral development Addresses aspects of Kant's ethical theor
Includes bibliographical references and index
Keywords: Aesthetics; Ethics; Kant, Immanuel, -- 1724-1804.; Electronic books